2010
DOI: 10.1007/s00268-010-0641-y
|View full text |Cite
|
Sign up to set email alerts
|

Is Hypoalbuminemia an Independent Prognostic Factor in Patients with Gastric Cancer?

Abstract: Low albumin concentrations are associated with poorer survival in patients with gastric cancer. However, the strength of this relation with survival is dependent on the presence of a systemic inflammatory response, as evidenced by an elevated CRP level. Therefore, it appears that the relation between hypoalbuminemia and poor survival is secondary to that of the systemic inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
111
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 35 publications
4
111
1
4
Order By: Relevance
“…In another study, Crumley et al (2006) indicated that low albumin was a confounding factor in the GPS scoring system. And Crumley also demonstrated that the development of hypo-albuminemia was secondary to an ongoing systemic inflammatory response and poor cancer specific survival was secondary to the systemic inflammatory response in patients with gastric cancer (Crumley et al, 2010). These results, from another perspective, showed that CRP is an effective marker to predict the prognosis for gastric cancer patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In another study, Crumley et al (2006) indicated that low albumin was a confounding factor in the GPS scoring system. And Crumley also demonstrated that the development of hypo-albuminemia was secondary to an ongoing systemic inflammatory response and poor cancer specific survival was secondary to the systemic inflammatory response in patients with gastric cancer (Crumley et al, 2010). These results, from another perspective, showed that CRP is an effective marker to predict the prognosis for gastric cancer patients.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, with the progression of cancer, the tumor itself can also trigger regional inflammatory response and release proinflammatory cytokines, which results in the formation of an inflammatory microenvironment (Balkwill et al, 2001;Coussens et al, 2002;Mantovani et al, 2008). Several studies pointed out that the elevated inflammatory response was associated with poor local immune response to the tumor and contributed to the lymph node spread and metastasis through a series of steps, including recruitment of the regulatory T lymphocytes and chemokine, activation of cytokines interleukin-6 and tumor necrosis factor-alpha, induction of neutrophilia, and secretion of CRP (Ulich et al, 1987;Ulich et al, 1989;Heikkila et al, 2007;Crumley et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies indicate that elevated CRP is a predictor of poor prognosis in malignant tumors including gastric cancer (Crumley et al, 2010;He et al, 2013;Szkandera et al, 2013;Xia et al, 2013). Serum concentration of CRP in tumor-bearing patients is known to be upregulated by proinflammatory cytokines including interleukin-1, interleukin-6, and tumor necrosis factor (Mahmoud et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, hypoalbunemia is reported to be associated with poor survival (Crumley et al, 2010;Jiang et al, 2012). Evidence also suggested that the development of hypoalbuminemia was a consequence of systemic inflammation, and might be secondary to elevation of CRP (Al-Shaiba et al, 2004;Onate-Ocana et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased prealbumin level is known to be an independent risk factor in cancer patients and its use is recommended in terminal cancer patients [19]. Similarly, hypo-albuminemia is a typical index of malnutrition and has been associated with poor prognosis in patients with advanced cancers [20].…”
Section: Discussionmentioning
confidence: 99%